Hybrid Identity: A Byproduct of Cross-Cultural Dynamics in While the Gods were Sleeping (Patan Pragya, 2024)
This paper deals with the hybrid identity of the protagonist caused by cross-cultural dynamics in While the Gods were Sleeping. This book is a memoir by Elizabeth Enslin, an American anthropologist and PhD scholar that narrates an exciting account of her journey to Nepal and experiences of living in Nepal and navigating the complexities of culture, love, and identity. The narrative focuses on love and marriage between Elizabeth Enslin (an American) and Pramod Parajuli (a Nepalese) in the book reflecting cross-cultural dynamics. Unlike the trend of South Asian males or females doing cross-cultural marriage in the west due to migration, the book is set up against the backdrop of increasing political turmoil in Nepal and narrates how an American woman develops hybrid identity facing the challenges of cross-cultural marriage, birth and childbearing in a foreign culture. In the process of exploring the impact of cross-cultural dynamics on the new identity formation of Enslin, this paper tries to address causes of migration, the effects of migration on her identity and the impact of cross-cultural dynamics on her changing aspect of identity. The major objective of the study is to examine how her identity is transformed for shaping new cultural identities in the diaspora. For the analytical purpose, Homi K. Bhabha’s theoretical concept of ‘third space’ is applied. Bhabha regards the hybrid third space as an ambivalent site where cultural meaning and representation have no “primordial unity or fixity” (176). Besides, Stuart Hall’s concept of cultural identity is also adopted. Thus, this paper tries to explore that the narrator’s cultural identity in the third space is hybridized due to cross-cultural activities.